Anti-corrosion oil and anti-corrosion material as well as preparation method and application thereof

By using anticorrosion oil containing monoalkoxy titanate and modified nanosilica, combined with hydraulic pressing technology, an anticorrosion bottom oil layer, intermediate fiber layer and outer protective layer of anticorrosion materials is formed, which solves the problem of insufficient weather resistance and impact resistance of steel structure protective materials in the marine environment, and achieves efficient corrosion protection of marine steel piles.

CN119955550APending Publication Date: 2025-05-09CHINA NAT PETROLEUM CORP +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311481218.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-08
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The protective materials used in steel structures in the prior art in marine environments have problems such as insufficient weather resistance, seawater corrosion resistance and impact resistance, resulting in shortening of the service life of the steel structure and high maintenance costs.

Method used

A preservative oil containing monoalkoxy titanate, modified nanosilica, nanotitanium dioxide, graphene and aluminum tripolyphosphate is used to form an anticorrosive bottom oil layer, an intermediate fiber layer and an outer protective layer, and combined with hydraulic pressing technology, the tight bonding and efficient protection of each layer are achieved.

Benefits of technology

It achieves good weather resistance, seawater corrosion resistance and impact resistance of anticorrosion materials, ensures long-term corrosion protection of marine steel piles, simplifies the construction process, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004538286080000051
    Figure BDA0004538286080000051
  • Figure BDA0004538286080000061
    Figure BDA0004538286080000061
  • Figure BDA0004538286080000211
    Figure BDA0004538286080000211
Patent Text Reader

Abstract

The invention relates to the field of corrosion protection materials, and discloses anti-corrosion oil, an anti-corrosion material and a preparation method and application of the anti-corrosion oil and the anti-corrosion material. The anticorrosive oil is prepared from mono-alkoxy titanate, dihydroxy propyl octadecanoate, an organic silicon defoaming agent, an antioxidant, modified nano silicon dioxide, nano titanium dioxide, graphene and aluminum triphosphate. Wherein the contact angle between the monoalkoxy titanate and water is 105 to 125 degrees, and the hydrophobic rate of the monoalkoxy titanate is 98 to 100 percent; wherein the content of hydroxyl groups in the modified nano silicon dioxide is 0.1-0.5 / nm < 2 >, and the particle size of the modified nano silicon dioxide meets the following conditions: based on the particle size interval width of 5nm, the maximum particle size range is 10-15nm, and the ratio is 45-55wt%. An anti-corrosion material formed by the anti-corrosion oil has good weather resistance, seawater corrosion resistance and impact resistance, no gap exists between the layers, the sealing performance is good, and long-acting corrosion protection can be provided for the marine steel pile.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of corrosion protection materials, and in particular to an anti-corrosion oil and an anti-corrosion material, and a preparation method and application thereof. Background Art

[0002] The marine environment has a serious effect on the corrosion of steel materials. As the use time of offshore platforms, high-pile docks, offshore steel structures and other facilities increases, the surface protective layer is seriously damaged, causing corrosion of steel piles and steel structures. Corrosion thinning causes the bearing capacity of steel piles and steel structures to decrease, posing a threat to production safety. Existing anti-corrosion layers and other protective repair technologies have high requirements for surface treatment of offshore repair and maintenance, complex procedures, and relatively long operation time. The above reasons result in poor overall anti-corrosion repair effects and short protection time.

[0003] At present, the main methods for protecting marine steel structures are: coating with FRP and heavy anti-corrosion coating protection. Coated FRP has the advantages of light weight, high specific strength, excellent heat resistance, corrosion resistance, good impact resistance, and superior process performance. However, due to the strong rigidity of FRP, seawater will penetrate into the inner side of the sheath when using FRP sheath alone, making it difficult to achieve satisfactory protection effects. Heavy anti-corrosion coating protection is a commonly used practice at home and abroad. From years of use, heavy anti-corrosion coating protection has also exposed certain problems. First, heavy anti-corrosion coating has poor impact resistance and needs maintenance in a short period of time (about 1-2 years) after new construction or repair; second, on-site repair problems. Although there are now heavy anti-corrosion coatings that can be constructed underwater, from the results of on-site applications, on-site repairs are difficult to guarantee construction quality and fail to achieve the expected results.

[0004] In recent years, multi-layer petrolatum coating technology has been considered as an effective anti-corrosion method for metal pipes and piles. The multi-layer petrolatum coating technology includes an inner anti-corrosion layer and an outer protective layer. When using the multi-layer petrolatum coating technology, it is necessary to apply the primer to the metal surface of the pile body, and then wrap the middle layer with anti-corrosion or buffering function layer by layer, and finally wrap the outer polyethylene or glass fiber reinforced plastic, glass fiber and other materials tightly on the outermost layer through a hydraulic tensioning device. This construction method is complicated and time-consuming, and when the coating is not tight, there are still gaps between the layers, which may cause seawater infiltration and corrosion, affecting the service life; or use a mold to press and form an integrated mold to prepare a multi-layer anti-corrosion sleeve, such as the preparation method disclosed in CN106739189A. However, although the sleeve structure prepared by this method is convenient to use, its processing method can only use a fixed specification mold to prepare a single-size sleeve, which cannot match steel piles of many diameter sizes. If you want to match multiple types of steel piles, you need to prepare molds of corresponding diameter sizes, and the processing cost is high.

[0005] Based on the problems of existing technologies in marine environment steel protective materials, such as poor weather resistance, seawater corrosion resistance, and poor resistance to marine biological attachment, there is an urgent need to develop an anti-corrosion material with excellent performance. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems of weather resistance, seawater corrosion resistance and impact resistance of marine environment steel protective materials in the prior art, and to provide an anti-corrosion oil and anti-corrosion material and their preparation method and application.

[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides an anti-corrosion oil, wherein the anti-corrosion oil contains monoalkoxy titanate, dihydroxypropyl octadecanoate, silicone defoamer, antioxidant, modified nano-silicon dioxide, nano-titanium dioxide, graphene and aluminum tripolyphosphate; wherein the contact angle of the monoalkoxy titanate with water is 105°-125°, and the hydrophobicity is 98-100%; wherein the hydroxyl content of the modified nano-silicon dioxide is 0.1-0.5 / nm 2 The particle size of the modified nano-silica satisfies: based on a particle size interval width of 5 nm, the maximum particle size range is 10-15 nm and accounts for 45-55% by weight.

[0008] The second aspect of the present invention provides an anti-corrosion material, wherein the anti-corrosion material comprises an anti-corrosion base oil layer, an intermediate fiber layer and an outer protective layer, wherein the anti-corrosion oil forming the anti-corrosion base oil layer is the anti-corrosion oil described in the first aspect.

[0009] The third aspect of the present invention provides a method for preparing an anti-corrosion material, wherein the preparation method comprises: laying an outer protective layer and an intermediate fiber layer and then pressing them, and after pressing is completed, coating an anti-corrosion base oil layer on the intermediate fiber layer, wherein the anti-corrosion oil forming the base oil layer is the anti-corrosion oil described in the first aspect.

[0010] The fourth aspect of the present invention provides an anti-corrosion material obtained by the preparation method.

[0011] A fifth aspect of the present invention provides an application of the anti-corrosion material in corrosion protection of marine steel materials.

[0012] Through the above technical solution, the present invention provides an anti-corrosion oil and an anti-corrosion material and a preparation method and application thereof, which have at least the following beneficial effects:

[0013] (1) The components of the anti-corrosion oil of the present invention cooperate with each other and have good synergistic effects, and the bottom oil layer formed has good seawater corrosion resistance, weather resistance, and impact resistance.

[0014] (2) The anti-corrosion material formed by the anti-corrosion oil of the present invention has good weather resistance, seawater corrosion resistance and impact resistance, has good gap-free sealing between the layers, and can provide long-term corrosion protection for marine steel piles.

[0015] (3) In a preferred embodiment, the preparation method of the anti-corrosion material of the present invention is simple and does not require special equipment. No bonding aid needs to be added during the pressing process. Under a specific pressure, each layer is fully bonded and has a specific thickness, so that the material can meet the sealing requirements and the rigidity, flexibility, tensile strength and impact buffering performance requirements required for being installed on the outside of a steel pile.

[0016] (4) The preparation and construction of the anti-corrosion material of the present invention is convenient and can be carried out manually. Compared with the original three-layer coating protection structure, it saves at least about 60% of the on-site construction time.

[0017] (5) The anti-corrosion material of the present invention has strong adaptability and can be cut, installed and used according to the sizes of steel piles of different specifications, with low processing cost and reduced material waste. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] The first aspect of the present invention provides an anti-corrosion oil, wherein the anti-corrosion oil contains monoalkoxy titanate, dihydroxypropyl octadecanoate, silicone defoamer, antioxidant, modified nano-silicon dioxide, nano-titanium dioxide, graphene and aluminum tripolyphosphate; wherein the contact angle of the monoalkoxy titanate with water is 105°-125°, and the hydrophobicity is 98-100%; wherein the hydroxyl content of the modified nano-silicon dioxide is 0.1-0.5 / nm 2 The particle size of the modified nano-silica satisfies: based on a particle size interval width of 5 nm, the maximum particle size range is 10-15 nm and accounts for 45-55% by weight.

[0020] In the present invention, the anticorrosive oil contains monoalkoxy titanate, dihydroxypropyl octadecanoate, silicone defoamer, antioxidant, modified nano silicon dioxide, nano titanium dioxide, graphene and aluminum tripolyphosphate. The components cooperate with each other and have good synergistic effects. The bottom oil layer formed has good seawater corrosion resistance, weather resistance and impact resistance. The contact angle of the monoalkoxy titanate with water is 105°-125°, and the hydrophobicity is 98-100%; the hydroxyl content of the modified nano silicon dioxide is 0.1-0.5 / nm. 2 , the particle size of the modified nano-silica satisfies: based on the particle size interval width of 5nm, the maximum particle size range is 10-15nm and the proportion is 45-55% by weight. When the relevant parameters of the monoalkoxy titanate and the modified nano-silica are within the above range, the anti-corrosion material formed by the anti-corrosion oil has good weather resistance, seawater corrosion resistance and impact resistance, and the gap-free sealing between the layers is good, which can provide long-term corrosion protection for marine steel piles.

[0021] In some specific embodiments of the present invention, the particle size of the modified nano-silicon dioxide satisfies: based on the particle size interval width of 5nm, the maximum particle size range is 10-15nm and the proportion is 45-55% by weight. The particle size described in the present invention is divided into less than or equal to 5nm, greater than 5nm and less than or equal to 10nm, greater than 10nm and less than or equal to 15nm, greater than 15nm and less than or equal to 20nm, greater than 20nm and less than or equal to 25nm, and so on. The particle size defined in this application is greater than 10nm and less than or equal to 15nm.

[0022] In some specific embodiments of the present invention, the alkoxy group in the monoalkoxy titanate is C5-C 10 The alkoxy group is preferably 2,6-dimethyl-4-heptyloxy. Monoalkoxy titanate is used as the base resin of the anti-corrosion oil. It has good water resistance, acid and alkali resistance, weather resistance and aging resistance. The anti-corrosion material formed by monoalkoxy titanate as anti-corrosion oil has good weather resistance, seawater corrosion resistance and impact resistance. There is no gap between the layers and the sealing is good, which can provide long-term corrosion protection for marine steel piles.

[0023] In some specific embodiments of the present invention, the modified nano-silica is nano-silica modified with arylsilazane.

[0024] In some specific embodiments of the present invention, 2,6-dimethyl-4-heptanol is used to modify titanium metal to obtain the monoalkoxy titanate, and the preparation method of the monoalkoxy titanate is: TiCl4 and 2,6-dimethyl-4-heptanol are modified under ZnO catalysis to obtain the monoalkoxy titanate. The reaction formula is:

[0025]

[0026] Among them, the structure of ROH is

[0027] Monoalkoxy titanate, as the base resin of anti-corrosion oil, has better water resistance, acid and alkali resistance, weather resistance and aging resistance compared to ordinary C9 resin. The anti-corrosion material formed by monoalkoxy titanate as anti-corrosion oil has good weather resistance, seawater corrosion resistance and impact resistance. There is no gap between the layers and the sealing is good, which can provide long-term corrosion protection for marine steel piles.

[0028] In some specific embodiments of the present invention, during the preparation of the monoalkoxy titanate, the molar ratio of the 2,6-dimethyl-4-heptanol to TiCl4 is 3-5:1, the pH of the modification reaction is 9-10, the temperature of the modification reaction is 150°C-180°C, and the time of the modification reaction is 1-2h. The monoalkoxy titanate formed when the temperature of the modification reaction is within this range has a higher hydrophobicity. When the pH of the modification reaction is 9-10, the monoalkoxy titanate formed has a higher hydrophobicity.

[0029] In some specific embodiments of the present invention, the preparation method of the modified nano-silica is: under nitrogen conditions, fumed silica and 1,3-diphenyltetramethyldisilazane are subjected to a hydroxyl substitution reaction to obtain the modified nano-silica. The modified nano-silica can avoid the agglomeration of fumed silica and improve its dispersibility and compatibility in the preservative oil. The reaction formula is:

[0030]

[0031] In some specific embodiments of the present invention, in the preparation of the modified nano-silica, the temperature of the hydroxyl replacement reaction is 120°C-180°C, the time of the hydroxyl replacement reaction is 30min-50min, and the molar ratio of fumed silica to 1,3-diphenyltetramethyldisilazane is 1-3:1. When the temperature of the hydroxyl replacement reaction of the modified nano-silica is 120°C-180°C, the hydroxyl content of the formed modified nano-silica is 0.1-0.5 / nm 2 , accounting for the largest particle size range of 45%-55% (10-15nm).

[0032] In some specific embodiments of the present invention, the organosilicon defoamer is selected from one or more of polydimethylsiloxane and polyethylene glycol siloxane, preferably polydimethylsiloxane, wherein the molecular weight of the organosilicon defoamer is 2000-3000 g / mol.

[0033] In some specific embodiments of the present invention, the antioxidant is selected from one or more of thiodiphenylamine, diphenylamine, and diisooctyldiphenylamine, preferably thiodiphenylamine.

[0034] In some specific embodiments of the present invention, relative to 1 part by weight of the monoalkoxy titanate, the content of the dihydroxypropyl octadecanoate is 0.1-0.3 parts by weight, the content of the organosilicon defoamer is 0.01-0.03 parts by weight, the content of the antioxidant is 0.01-0.03 parts by weight, the content of the modified nano-silicon dioxide is 0.01-0.03 parts by weight, the content of the nano-titanium dioxide is 0.01-0.03 parts by weight, the content of the graphene is 0.01-0.03 parts by weight, and the content of the aluminum tripolyphosphate is 0.01-0.03 parts by weight. The anticorrosive oil formed by the components in the above range has good seawater corrosion resistance and marine biofouling resistance, and impact resistance.

[0035] In some specific embodiments of the present invention, the components of the anti-corrosion oil can be ground after being evenly mixed to evenly disperse the filler particles, so that the anti-corrosion oil can better adhere to the surface of the steel pile, improve the adhesion and durability of the anti-corrosion oil, and thus improve the corrosion resistance and durability of the anti-corrosion base oil.

[0036] In some specific embodiments of the present invention, the components of the preservative oil may be sieved through a 1200 mesh sieve before mixing.

[0037] The second aspect of the present invention provides an anti-corrosion material, wherein the anti-corrosion material comprises an anti-corrosion base oil layer, an intermediate fiber layer and an outer protective layer, wherein the anti-corrosion oil forming the anti-corrosion base oil layer is the anti-corrosion oil described in the first aspect.

[0038] In some specific embodiments of the present invention, the intermediate fiber layer is selected from one or more fiber layers formed by polyester fiber, polyurethane fiber and polyamide fiber. The intermediate fiber layer is selected from polyester fiber, polyurethane fiber and polyamide fiber, which have the advantages of good aging resistance and tensile resistance.

[0039] In some specific embodiments of the present invention, in the outer protective layer, relative to 100 parts by weight of polyethylene, the content of ethylene-vinyl acetate copolymer is 0.1-0.3 parts by weight, the content of benzotriazole is 0.2-0.8 parts by weight, the content of thiocarbamate is 0.3-0.6 parts by weight, the content of graphene is 5-10 parts by weight, the content of silicon micropowder is 6-10 parts by weight, the content of neodymium oxide is 2-5 parts by weight, and the content of aluminum tripolyphosphate is 0.1-0.5 parts by weight. After the components of the outer protective layer are evenly mixed, they can be made into sheets by hot melt extrusion for standby use. Preferably, the molecular weight of the polyethylene is 2000-3000g / mol; preferably, the molecular weight of the ethylene-vinyl acetate copolymer is 1000-3000g / mol. Preferably, the weight ratio of the structural units provided by ethylene to the structural units provided by vinyl acetate in the ethylene-vinyl acetate copolymer is 70-75:25-30.

[0040] In some specific embodiments of the present invention, the thickness of the base oil layer is 2-3 mm, the thickness of the intermediate fiber layer is 2-3 mm, and the thickness of the outer protective layer is 2-5 mm.

[0041] The hydrophobicity of the base oil layer is 96%-98.8%, the tensile strength of the intermediate fiber layer is 10MPa-12MPa, the elongation at break of the intermediate fiber layer is 10%-15%, the elongation at break of the outer protective layer is 730%-760%, the tensile strength of the outer protective layer is 28MPa-31MPa, the impact strength of the outer protective layer is 8J / mm, and the 3000h UV aging resistance tensile performance retention rate of the outer protective layer is 84-87%.

[0042] No volatile solvent is added to the bottom oil layer, and the solid content of the bottom oil layer is 100%.

[0043] The anti-corrosion material formed by the anti-corrosion oil of the present invention has good weather resistance, seawater corrosion resistance and marine biofouling resistance, is impact resistant, has good gap-free sealing between layers, and can provide long-term corrosion protection for marine steel piles.

[0044] The third aspect of the present invention provides a method for preparing an anti-corrosion material, wherein the preparation method comprises: laying an outer protective layer and an intermediate fiber layer in sequence and then pressing them, and coating an anti-corrosion base oil layer on the intermediate fiber layer after the pressing is completed. The anti-corrosion oil forming the base oil layer is the anti-corrosion oil described in the first aspect. The specific types or thicknesses of the outer protective layer and the intermediate fiber layer are as described above and will not be repeated here.

[0045] In some specific embodiments of the present invention, the pressing method is hydraulic pressing.

[0046] In some specific embodiments of the present invention, the temperature of the hydraulic pressing is 50°C-90°C, and the pressure is 10MPa-20MPa. The specific process of the hydraulic pressing is: placing the outer protective layer and the middle fiber layer on the surface of the hydraulic press in sequence, and then applying pressure to press the two layers into one layer. After the pressing is completed, an anti-corrosion base oil layer is applied on the middle fiber layer. No adhesive additive is required to be added during the pressing process of the present invention.

[0047] In some specific embodiments of the present invention, the preparation method comprises:

[0048] (1) monoalkoxy titanate, dihydroxypropyl octadecanoate, silicone defoamer, antioxidant, modified nano silicon dioxide, nano titanium dioxide, graphene and aluminum tripolyphosphate are mixed and ground to obtain a base oil layer;

[0049] (2) mixing polyethylene, ethylene-vinyl acetate copolymer, benzotriazole, thiocarbamate, graphene, silicon micropowder, and neodymium oxide, and hot-melt extruding to obtain a sheet to obtain an outer protective layer;

[0050] (3) Laying the outer protective layer, the middle fiber layer and the bottom oil layer in sequence, and obtaining the anti-corrosion material by hydraulic pressing.

[0051] The fourth aspect of the present invention provides an anti-corrosion material obtained by the preparation method.

[0052] A fifth aspect of the present invention provides an application of the anti-corrosion material in corrosion protection of marine steel materials.

[0053] In some specific embodiments of the present invention, the steel pile is cut to size according to its diameter during use, and the cut side length of the coating anti-corrosion material is smaller than the circumference of the steel pile during cutting. Flanges are welded on the outer protective surface of both sides of the single-layer coating anti-corrosion material obtained after cutting.

[0054] In some specific embodiments of the present invention, during installation, at the anti-corrosion site, the surface of the steel pile is first cleaned. After the cleaning meets the standard requirements, the cut anti-corrosion coating material is directly wrapped on the surface of the steel pile. Since the cut side length of the anti-corrosion coating material is smaller than the circumference of the steel pile, there is still a certain circumferential distance between the two flanges after wrapping. Use hydraulic tools, such as a hydraulic wrench, to fit the flanges together, and then tighten them with 316L stainless steel bolts.

[0055] The present invention will be described in detail below through examples.

[0056] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.

[0057] Example 1

[0058] Preparation of monoalkoxy titanate: Add 1 part of 2,6-dimethyl-4-heptanol into a reactor, add TiCl4 and ZnO, the molar ratio of 2,6-dimethyl-4-heptanol to TiCl4 is 4:1, ZnO is 0.01 parts, adjust the pH of the reaction system to 9.0, the temperature is 150°C, the reaction time is 1h, and the monoalkoxy titanate is separated.

[0059] Preparation of modified nano-silica: Add 1 part of fumed silica into the modification device, heat it under the condition of nitrogen, the heating temperature is 140°C, the time is 40 minutes, add 1,3-diphenyltetramethyldisilazane, the molar ratio of fumed silica to 1,3-diphenyltetramethyldisilazane is 2:1. Under the protection of nitrogen, fumed silica and 1,3-diphenyltetramethyldisilazane undergo hydroxyl substitution reaction to generate modified nano-silica.

[0060] Preparation of the bottom oil layer: In a stainless steel barrel, add 1 part of monoalkoxy titanate and 0.2 parts of dihydroxypropyl octadecanoate, mix and stir at high speed at room temperature, add 0.02 parts of chemically pure polydimethylsiloxane (molecular weight 2600g / mol, the same below), 0.03 parts of chemically pure thiodiphenylamine, 0.03 parts of modified nano-silicon dioxide, 0.2 parts of nano-titanium dioxide, 0.2 parts of graphene, 0.1 parts of 1200 mesh aluminum tripolyphosphate, stir at high speed for 0.5 hours, and grind with a sand mill for 0.5 hours. The amount of each component is measured by weight.

[0061] Preparation of outer protective layer: 100 parts of polyethylene (molecular weight of 2500g / mol, the same below), 0.2 parts of ethylene-vinyl acetate copolymer (molecular weight of 2800g / mol, the weight ratio of the structural unit provided by ethylene to the structural unit provided by vinyl acetate in the ethylene-vinyl acetate copolymer is 70:30, the same below), 0.4 parts of benzotriazole, 0.5 parts of thiocarbamate, 8 parts of graphene, 8 parts of 1200 mesh silicon powder, 3 parts of neodymium oxide are sequentially placed in a mixing barrel, and dispersed at high speed for more than 5 minutes with a disperser at a temperature of about 50°C to mix the above materials evenly, and then formed into a sheet by hot melt extrusion. The amount of each component is measured by weight.

[0062] Preparation of anti-corrosion materials: Place an outer protective layer of 3mm and a middle polyester fiber layer of 2.5mm on the surface of the hydraulic press in sequence. At a temperature of 75°C, use a hydraulic press with a pressure controlled at 15MPa to press the two layers of material into one layer. After pressing, apply 2.5mm of anti-corrosion primer on the middle fiber layer. The total thickness is 8.0mm. No adhesive additives are added during the pressing process.

[0063] Example 2

[0064] Preparation of monoalkoxy titanate: Add 1 part of 2,6-dimethyl-4-heptanol into the reactor, add TiCl4 and ZnO, the molar ratio of 2,6-dimethyl-4-heptanol to TiCl4 is 4:1, ZnO is 0.02 parts, adjust the pH of the reaction system to 10.0, the temperature is 180°C, the reaction time is 2h, and monoalkoxy titanate is generated.

[0065] Preparation of modified nano-silica: Add 1 part of fumed silica into the modification device, heat it under the condition of nitrogen, the heating temperature is 120°C, the time is 30 minutes, add 1,3-diphenyltetramethyldisilazane, the molar ratio of fumed silica to 1,3-diphenyltetramethyldisilazane is 2:1. Under the protection of nitrogen, fumed silica and 1,3-diphenyltetramethyldisilazane undergo hydroxyl substitution reaction to generate modified nano-silica.

[0066] Preparation of the bottom oil layer: add 1 part of monoalkoxy titanate and 0.1 part of dihydroxypropyl octadecanoate to a stainless steel barrel, mix and stir at high speed at room temperature, add 0.01 part of chemically pure polydimethylsiloxane, 0.01 part of chemically pure thiodiphenylamine, 0.01 part of modified nano-silicon dioxide, 0.1 part of nano-titanium dioxide, 0.1 part of graphene, 0.1 part of 1000 mesh aluminum tripolyphosphate, stir at high speed for 0.5 hours, and grind with a sand mill for 0.5 hours. The amount of each component is measured by weight.

[0067] Preparation of outer protective layer: Add 100 parts of high-density polyethylene and 0.1 parts of ethylene-vinyl acetate copolymer into a stainless steel barrel, mix them, add 0.2 parts of ultraviolet light stabilizer benzotriazole and 0.3 parts of thiocarbamate while stirring, control the temperature at 25°C, stir at high speed, add 5 parts of graphene, 6 parts of 1200 mesh silicon powder, and 2 parts of neodymium oxide while stirring, stir at high speed for 5 minutes, and then make a sheet by hot melt extrusion. The amount of each component is measured by weight.

[0068] Preparation of anti-corrosion materials: Place a 2mm outer protective layer and a 2mm middle polyester fiber layer on the surface of the hydraulic press in sequence. At a temperature of 50°C, use a hydraulic press with a pressure controlled at 10MPa to press the two layers of material into one layer. After pressing, apply 2.5mm of anti-corrosion primer on the middle fiber layer. The total thickness is 6.5mm. No adhesive additive is needed during the pressing process.

[0069] Example 3

[0070] Preparation of monoalkoxy titanate: Add 1 part of 2,6-dimethyl-4-heptanol into the reactor, add TiCl4 and ZnO, the molar ratio of 2,6-dimethyl-4-heptanol to TiCl4 is 4:1, ZnO is 0.05 parts, adjust the pH of the reaction system to 9.5, the temperature is 170°C, the reaction time is 1.5h, and monoalkoxy titanate is generated.

[0071] Preparation of modified nano-silica: Add 1 part of fumed silica into the modification device, heat it under the condition of nitrogen, the heating temperature is 180°C, the time is 50 minutes, add 1,3-diphenyltetramethyldisilazane, the molar ratio of fumed silica to 1,3-diphenyltetramethyldisilazane is 2:1. Under the protection of nitrogen, fumed silica and 1,3-diphenyltetramethyldisilazane undergo hydroxyl substitution reaction to generate modified nano-silica.

[0072] Preparation of the bottom oil layer: add 1 part of monoalkoxy titanate and 0.3 part of dihydroxypropyl octadecanoate to a stainless steel barrel, mix and stir at high speed at room temperature, add 0.03 part of chemically pure polydimethylsiloxane, 0.04 part of chemically pure thiodiphenylamine, 0.04 part of modified nano-silicon dioxide, 0.5 part of nano-titanium dioxide, 0.5 part of graphene, 0.5 part of 1000 mesh aluminum tripolyphosphate, stir at high speed for 0.5h, and grind with a sand mill for 0.5h to prepare. The amount of each component is measured by weight.

[0073] Preparation of outer protective layer: Add 100 parts of polyethylene and 0.3 parts of ethylene-vinyl acetate copolymer into a stainless steel barrel, mix them, add 0.8 parts of ultraviolet light stabilizer benzotriazole and 0.6 parts of thiocarbamate while stirring, control the temperature at 25°C, stir at high speed, add 10 parts of graphene, 10 parts of 1200 mesh silicon powder, and 5 parts of neodymium oxide while stirring, stir at high speed for 5 minutes, and then make a sheet by hot melt extrusion. The amount of each component is measured by weight.

[0074] Preparation of anti-corrosion materials: Place an outer protective layer of 5mm and a middle polyester fiber layer of 3mm on the surface of the hydraulic press in sequence. At a temperature of 90°C, use a hydraulic press with a pressure controlled at 20MPa to press the two layers of material into one layer. After pressing, apply 3mm of anti-corrosion primer on the middle fiber layer. The total thickness is 11mm. No adhesive additive is needed during the pressing process.

[0075] Example 4

[0076] Preparation of monoalkoxy titanate: Add 1 part of 2,6-dimethyl-4-heptanol into the reactor, add TiCl4 and ZnO, the molar ratio of 2,6-dimethyl-4-heptanol to TiCl4 is 4:1, ZnO is 0.03 parts, adjust the pH of the reaction system to 9.8, the temperature is 160°C, the reaction time is 2h, and monoalkoxy titanate is generated.

[0077] Preparation of modified nano-silica: Add 1 part of fumed silica into the modification device, heat it under the condition of nitrogen, the heating temperature is 140°C, the time is 40 minutes, add 1,3-diphenyltetramethyldisilazane, the molar ratio of fumed silica to 1,3-diphenyltetramethyldisilazane is 2:1. Under the protection of nitrogen, fumed silica and 1,3-diphenyltetramethyldisilazane undergo hydroxyl substitution reaction to generate modified nano-silica.

[0078] Preparation of the bottom oil layer: add 1 part of monoalkoxy titanate and 0.2 parts of dihydroxypropyl octadecanoate to a stainless steel barrel, mix and stir at high speed at room temperature, add 0.02 parts of chemically pure polydimethylsiloxane, 0.03 parts of chemically pure thiodiphenylamine, 0.03 parts of modified nano-silicon dioxide, 0.2 parts of nano-titanium dioxide, 0.2 parts of graphene, 0.1 parts of 1200 mesh aluminum tripolyphosphate, stir at high speed for 0.5 hours, and grind with a sand mill for 0.5 hours to prepare. The amount of each component is measured by weight.

[0079] Preparation of outer protective layer: 100 parts of polyethylene, 0.2 parts of ethylene-vinyl acetate copolymer, 0.4 parts of UV stabilizer benzotriazole, 0.5 parts of thiocarbamate, 8 parts of graphene, 8 parts of 1200 mesh silicon powder, 3 parts of neodymium oxide are sequentially placed in a mixing barrel, and dispersed at high speed for more than 5 minutes at a temperature of about 50°C using a disperser to mix the above materials evenly, and then formed into sheets by hot melt extrusion. The amount of each component is measured by weight.

[0080] Preparation of anti-corrosion materials: Place a 2mm outer protective layer and a 2mm middle polyurethane fiber layer on the surface of the hydraulic press in sequence. At a temperature of 50°C, use a hydraulic press with a pressure controlled at 10MPa to press the two layers of material into one layer. After pressing, apply 2.5mm of anti-corrosion primer on the middle fiber layer. The total thickness is 6.5mm. No adhesive additive is needed during the pressing process.

[0081] Example 5

[0082] Preparation of monoalkoxy titanate: Add 1 part of 2,6-dimethyl-4-heptanol into the reactor, add TiCl4 and ZnO, the molar ratio of 2,6-dimethyl-4-heptanol to TiCl4 is 4:1, ZnO is 0.04 parts, adjust the pH of the reaction system to 9.2, the temperature is 160°C, the reaction time is 1h, and monoalkoxy titanate is generated.

[0083] Preparation of modified nano-silica: Add 1 part of fumed silica into the modification device, heat it under the condition of nitrogen, the heating temperature is 140°C, the time is 40 minutes, add 1,3-diphenyltetramethyldisilazane, the molar ratio of fumed silica to 1,3-diphenyltetramethyldisilazane is 2:1. Under the protection of nitrogen, fumed silica and 1,3-diphenyltetramethyldisilazane undergo hydroxyl substitution reaction to generate modified nano-silica.

[0084] Preparation of the bottom oil layer: add 1 part of monoalkoxy titanate and 0.2 parts of dihydroxypropyl octadecanoate to a stainless steel barrel, mix and stir at high speed at room temperature, add 0.02 parts of chemically pure polydimethylsiloxane, 0.03 parts of chemically pure thiodiphenylamine, 0.03 parts of modified nano-silicon dioxide, 0.2 parts of nano-titanium dioxide, 0.2 parts of graphene, 0.1 parts of 1200 mesh aluminum tripolyphosphate, stir at high speed for 0.5 hours, and grind with a sand mill for 0.5 hours to prepare. The amount of each component is measured by weight.

[0085] Preparation of outer protective layer: 100 parts of polyethylene, 0.2 parts of ethylene-vinyl acetate copolymer, 0.4 parts of benzotriazole, 0.5 parts of thiocarbamate, 8 parts of graphene, 8 parts of 1200 mesh silicon powder, and 3 parts of neodymium oxide are sequentially placed in a mixing barrel, and dispersed at high speed for more than 5 minutes at a temperature of about 50°C using a disperser to mix the above materials evenly, and then formed into a sheet by hot melt extrusion. The amount of each component is measured by weight.

[0086] Preparation of anti-corrosion materials: Place an outer protective layer of 5mm and a middle polyurethane fiber layer of 3mm on the surface of the hydraulic press in sequence. At a temperature of 90°C, use a hydraulic press with a pressure controlled at 20MPa to press the two layers of material into one layer. After pressing, apply 3mm anti-corrosion primer on the middle fiber layer with a total thickness of 11mm. No adhesive additive is needed during the pressing process.

[0087] Example 6

[0088] Preparation of monoalkoxy titanate: Add 1 part of 2,6-dimethyl-4-heptanol into the reactor, add TiCl4 and ZnO, the molar ratio of 2,6-dimethyl-4-heptanol to TiCl4 is 4:1, ZnO is 0.01 part, adjust the pH of the reaction system to 9.0, the temperature is 150°C, the reaction time is 2h, and monoalkoxy titanate is generated.

[0089] Preparation of modified nano-silica: Add 1 part of fumed silica into the modification device, heat it under the condition of nitrogen, the heating temperature is 120°C, the time is 30 minutes, add 1,3-diphenyltetramethyldisilazane, the molar ratio of fumed silica to 1,3-diphenyltetramethyldisilazane is 2:1. Under the protection of nitrogen, fumed silica and 1,3-diphenyltetramethyldisilazane undergo hydroxyl substitution reaction to generate modified nano-silica.

[0090] Preparation of the bottom oil layer: add 1 part of monoalkoxy titanate and 0.1 part of dihydroxypropyl octadecanoate to a stainless steel barrel, mix and stir at high speed at room temperature, add 0.01 part of chemically pure polydimethylsiloxane, 0.01 part of chemically pure thiodiphenylamine, 0.01 part of modified nano-silicon dioxide, 0.1 part of nano-titanium dioxide, graphene, and 0.1 part of 1000 mesh aluminum tripolyphosphate, stir at high speed for 0.5 hours, and grind with a sand mill for 0.5 hours. The amount of each component is measured by weight.

[0091] Preparation of outer protective layer: Add 100 parts of high-density polyethylene and 0.1 parts of ethylene-vinyl acetate copolymer into a stainless steel barrel, mix them, add 0.2 parts of ultraviolet light stabilizer benzotriazole and 0.3 parts of thiocarbamate while stirring, control the temperature at 25°C, stir at high speed, add 5 parts of graphene, 6 parts of 1200 mesh silicon powder, and 2 parts of neodymium oxide while stirring, stir at high speed for 5 minutes, and then make a sheet by hot melt extrusion. The amount of each component is measured by weight.

[0092] Preparation of anti-corrosion materials: Place an outer protective layer of 3mm and a middle polyurethane fiber layer of 2.5mm on the surface of the hydraulic press in sequence. At a temperature of 75°C, use a hydraulic press with a pressure controlled at 15MPa to press the two layers of material into one layer. After pressing, apply 2.5mm of anti-corrosion primer on the middle fiber layer. The total thickness is 8.0mm. No adhesive additives are added during the pressing process.

[0093] Example 7

[0094] Preparation of monoalkoxy titanate: Add 1 part of 2,6-dimethyl-4-heptanol into the reactor, add TiCl4 and ZnO, the molar ratio of 2,6-dimethyl-4-heptanol to TiCl4 is 4:1, ZnO is 0.04 parts, adjust the pH of the reaction system to 9.6, the temperature is 165°C, the reaction time is 1.8h, and monoalkoxy titanate is generated.

[0095] Preparation of modified nano-silica: Add 1 part of fumed silica into the modification device, heat it under the condition of nitrogen, the heating temperature is 120°C, the time is 30 minutes, add 1,3-diphenyltetramethyldisilazane, the molar ratio of fumed silica to 1,3-diphenyltetramethyldisilazane is 2:1. Under the protection of nitrogen, fumed silica and 1,3-diphenyltetramethyldisilazane undergo hydroxyl substitution reaction to generate modified nano-silica.

[0096] Preparation of the bottom oil layer: add 1 part of monoalkoxy titanate and 0.1 part of dihydroxypropyl octadecanoate to a stainless steel barrel, mix and stir at high speed at room temperature, add 0.01 part of chemically pure polydimethylsiloxane, 0.01 part of chemically pure thiodiphenylamine, 0.01 part of modified nano-silicon dioxide, 0.1 part of nano-titanium dioxide, 0.1 part of graphene, 0.1 part of 1000 mesh aluminum tripolyphosphate, stir at high speed for 0.5 hours, and grind with a sand mill for 0.5 hours. The amount of each component is measured by weight.

[0097] Preparation of outer protective layer: Add 100 parts of high-density polyethylene and 0.1 parts of ethylene-vinyl acetate copolymer into a stainless steel barrel, mix them, add 0.2 parts of ultraviolet light stabilizer benzotriazole and 0.3 parts of thiocarbamate while stirring, control the temperature at 25°C, stir at high speed, add 5 parts of graphene, 6 parts of 1200 mesh silicon powder, and 2 parts of neodymium oxide while stirring, stir at high speed for 5 minutes, and then make a sheet by hot melt extrusion. The amount of each component is measured by weight.

[0098] Preparation of anti-corrosion materials: Place an outer protective layer of 5mm and a middle polyamide fiber layer of 3mm on the surface of the hydraulic press in sequence. At a temperature of 90°C, use a hydraulic press with a pressure controlled at 20MPa to press the two layers of material into one layer. After pressing, apply 3mm of anti-corrosion primer on the middle fiber layer. The total thickness is 11mm. No adhesive additive is needed during the pressing process.

[0099] Example 8

[0100] Preparation of monoalkoxy titanate: Add 1 part of 2,6-dimethyl-4-heptanol into a reactor, add TiCl4 and ZnO, the molar ratio of 2,6-dimethyl-4-heptanol to TiCl4 is 4:1, ZnO is 0.01 part, adjust the pH of the reaction system to 10.0, the temperature is 165°C, the reaction time is 2.0h, and monoalkoxy titanate is generated.

[0101] Preparation of modified nano-silica: Add 1 part of fumed silica into the modification device, heat it under the condition of nitrogen, the heating temperature is 180°C, the time is 50 minutes, add 1,3-diphenyltetramethyldisilazane, the molar ratio of fumed silica to 1,3-diphenyltetramethyldisilazane is 2:1. Under the protection of nitrogen, fumed silica and 1,3-diphenyltetramethyldisilazane undergo hydroxyl substitution reaction to generate modified nano-silica.

[0102] Preparation of the bottom oil layer: add 1 part of monoalkoxy titanate and 0.3 parts of dihydroxypropyl octadecanoate to a stainless steel barrel, mix and stir at high speed at room temperature, add 0.03 parts of chemically pure polydimethylsiloxane, 0.04 parts of chemically pure thiodiphenylamine, 0.04 parts of modified nano-silicon dioxide, 0.5 parts of nano-titanium dioxide, and 0.5 parts of graphene while stirring, stir at high speed for 0.5 hours, and grind with a sand mill for 0.5 hours. The amount of each component is measured by weight.

[0103] Preparation of outer protective layer: Add 100 parts of high-density polyethylene and 0.3 parts of ethylene-vinyl acetate copolymer into a stainless steel barrel, mix them, add 0.8 parts of ultraviolet light stabilizer benzotriazole and 0.6 parts of thiocarbamate while stirring, control the temperature at 25°C, stir at high speed, add 10 parts of graphene, 10 parts of 1200 mesh silicon powder, and 5 parts of nano titanium dioxide while stirring, stir at high speed for 5 minutes, and then make a sheet by hot melt extrusion. The amount of each component is measured by weight.

[0104] Preparation of anti-corrosion materials: Place an outer protective layer of 3mm and a middle polyamide fiber layer of 2.5mm on the surface of the hydraulic press in sequence. At a temperature of 75°C, use a hydraulic press with a pressure controlled at 15MPa to press the two layers of material into one layer. After pressing, apply 2.5mm of anti-corrosion primer on the middle fiber layer. The total thickness is 8.0mm. No adhesive additives are added during the pressing process.

[0105] Example 9

[0106] Preparation of monoalkoxy titanate: Add 1 part of 2,6-dimethyl-4-heptanol into the reactor, add TiCl4 and ZnO, the molar ratio of 2,6-dimethyl-4-heptanol to TiCl4 is 4:1, ZnO is 0.01 parts, adjust the pH of the reaction system to 9.8, the temperature is 175°C, the reaction time is 1.8h, and monoalkoxy titanate is generated.

[0107] Preparation of modified nano-silica: Add 1 part of fumed silica into the modification device, heat it under the condition of nitrogen, the heating temperature is 180°C, the time is 50 minutes, add 1,3-diphenyltetramethyldisilazane, the molar ratio of fumed silica to 1,3-diphenyltetramethyldisilazane is 2:1. Under the protection of nitrogen, fumed silica and 1,3-diphenyltetramethyldisilazane undergo hydroxyl substitution reaction to generate modified nano-silica.

[0108] Preparation of the bottom oil layer: add 1 part of monoalkoxy titanate and 0.3 part of dihydroxypropyl octadecanoate to a stainless steel barrel, mix and stir at high speed at room temperature, add 0.03 part of chemically pure polydimethylsiloxane, 0.04 part of chemically pure thiodiphenylamine, 0.04 part of modified nano-silicon dioxide, 0.5 part of nano-titanium dioxide, 0.5 part of graphene, 0.5 part of 1000 mesh aluminum tripolyphosphate, stir at high speed for 0.5h, and grind with a sand mill for 0.5h to prepare. The amount of each component is measured by weight.

[0109] Preparation of outer protective layer: Add 100 parts of high-density polyethylene and 0.3 parts of ethylene-vinyl acetate copolymer into a stainless steel barrel, mix them, add 0.8 parts of ultraviolet light stabilizer benzotriazole and 0.6 parts of thiocarbamate while stirring, control the temperature at 25°C, stir at high speed, add 10 parts of graphene, 10 parts of 1200 mesh silicon powder, and 5 parts of nano titanium dioxide while stirring, stir at high speed for 5 minutes, and then make a sheet by hot melt extrusion. The amount of each component is measured by weight.

[0110] Preparation of anti-corrosion materials: Place a 2mm outer protective layer and a 2mm middle polyamide fiber layer on the surface of the hydraulic press in sequence. At a temperature of 50°C, use a hydraulic press with a pressure controlled at 10MPa to press the two layers of material into one layer. After pressing, apply 2.5mm of anti-corrosion primer on the middle fiber layer. The total thickness is 6.5mm. No adhesive additive is needed during the pressing process.

[0111] Example 10

[0112] The monoalkoxy titanate and the modified nano silicon dioxide were prepared according to the method of Example 1, except that, in the preparation of the bottom oil layer, 1 part of monoalkoxy titanate and 0.2 part of dihydroxypropyl octadecanoate were added, mixed and stirred at high speed under normal temperature, and 0.02 part of chemically pure polydimethylsiloxane, 0.03 part of chemically pure thiodiphenylamine, 0.1 part of modified nano silicon dioxide, 0.2 part of nano titanium dioxide, 0.2 part of graphene, and 0.1 part of 1200 mesh aluminum tripolyphosphate were added under stirring, and the mixture was stirred at high speed for 0.5h and then ground with a sand mill for 0.5h. The amount of each component was calculated by weight. The other conditions were the same as those in Example 1.

[0113] Embodiment 11

[0114] The monoalkoxy titanate and the modified nano silicon dioxide were prepared according to the method of Example 1, except that, in the preparation of the bottom oil layer, 0.8 parts of monoalkoxy titanate and 0.2 parts of dihydroxypropyl octadecanoate were added, mixed and stirred at high speed under normal temperature, and 0.02 parts of chemically pure polydimethylsiloxane, 0.03 parts of chemically pure thiodiphenylamine, 0.03 parts of modified nano silicon dioxide, 0.2 parts of nano titanium dioxide, 0.2 parts of graphene, and 0.1 parts of 1200 mesh aluminum tripolyphosphate were added under stirring, and the mixture was prepared by grinding with a sand mill for 0.5 hours after high-speed stirring for 0.5 hours. The amount of each component is calculated by weight. Other conditions are the same as those in Example 1.

[0115] Comparative Example 1

[0116] The monoalkoxy titanate was prepared according to the method of Example 1, except that the temperature was 140° C. to generate the monoalkoxy titanate. The other conditions were the same as those of Example 1.

[0117] Comparative Example 2

[0118] The monoalkoxy titanate was prepared according to the method of Example 1, except that the pH of the reaction system was adjusted to 7.0 to generate the monoalkoxy titanate. Other conditions were the same as those of Example 1.

[0119] Comparative Example 3

[0120] The monoalkoxy titanate was prepared according to the method of Example 1, except that the silicon dioxide was not modified, and the modified nano silicon dioxide was replaced by fumed silicon dioxide in the bottom oil layer. The other conditions were the same as those of Example 1.

[0121] Comparative Example 4

[0122] The modified nano-silicon dioxide was prepared according to the method of Example 1, except that the heating temperature was 100° C. to generate the modified nano-silicon dioxide. The other conditions were the same as those of Example 1.

[0123] Comparative Example 5

[0124] The modified nano-silica was prepared according to the method of Example 1, except that the heating temperature was 190° C. to generate the modified nano-silica. The other conditions were the same as those of Example 1.

[0125] Comparative Example 6

[0126] The modified nano-silica was prepared according to the method of Example 1, except that the monoalkoxy titanate was not modified, and C9 petroleum resin was used in the bottom oil layer instead of the monoalkoxy titanate. Other conditions were the same as those of Example 1.

[0127] The performance of the monoalkoxy titanate, modified nano-silica, base oil layer, intermediate fiber layer, outer protective layer and the obtained anti-corrosion material in the embodiments and comparative examples were tested respectively, and the test results are shown in Tables 1-3.

[0128] Test methods: solid content (SY / T0417); hydrophobicity (GB / T10299); tensile strength (GB / T1040.2); elongation at break (GB / T1040.2); elongation at break (GB / T1040.2); tensile strength (GB / T1040.2); impact strength (Appendix K of GB / T23257); resistance to ultraviolet aging (3000h) (Appendix J of GB / T23257), contact angle with water (GB / T 30693-2014); hydroxyl group of nano-silica (T / FSI 049-2020); particle size of silica (GB / T13221). Note: For example, the maximum particle size range is 10-15 (46.24%), which means that based on the particle size interval width of 5nm, the maximum particle size range is 10-15nm and accounts for 46.24% by weight.

[0129] Table 1

[0130]

[0131]

[0132] Table 2

[0133]

[0134] Table 3

[0135]

[0136]

[0137] From the results in Table 1-3, it can be seen that the monoalkoxy titanate of Examples 1-11 of the present invention has good hydrophobicity, the modified nano silica has a smaller particle diameter and surface hydroxyl content, can effectively avoid the agglomeration of fumed silica, the anticorrosive base oil has a high hydrophobicity, the middle fiber layer has good tensile strength, the outer protective layer has good tensile strength and impact resistance, and the single-layer coated anticorrosive material has good high temperature and high pressure water-resistant sealing performance. Compared with Comparative Examples 1-6, it has obviously better effects.

[0138] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An antiseptic oil, characterized in that: The anticorrosive oil contains monoalkoxy titanate, dihydroxypropyl octadecanoate, an organic silicon defoamer, an antioxidant, modified nano silicon dioxide, nano titanium dioxide, graphene and aluminum tripolyphosphate; The contact angle between the monoalkoxy titanate and water is 105°-125°, and the hydrophobicity is 98-100%. The hydroxyl content of the modified nano-silicon dioxide is 0.1-0.5 / nm. 2 The particle size of the modified nano-silica satisfies: based on a particle size interval width of 5 nm, the maximum particle size range is 10-15 nm and accounts for 45-55% by weight.

2. The antiseptic oil according to claim 1, wherein The alkoxy group in the monoalkoxy titanate is C5-C 10 An alkoxy group, preferably 2,6-dimethyl-4-heptyloxy; Preferably, 2,6-dimethyl-4-heptanol is used to modify titanium metal to obtain the monoalkoxy titanate; Preferably, the monoalkoxy titanate is prepared by: contacting TiCl4 with 2,6-dimethyl-4-heptanol under ZnO catalysis to carry out a modification reaction to obtain the monoalkoxy titanate; Preferably, the modified nano-silica is nano-silica modified with arylsilazane; More preferably, the preparation method of the modified nano-silica is: under nitrogen conditions, fumed silica is contacted with 1,3-diphenyltetramethyldisilazane to carry out a hydroxyl replacement reaction to obtain the modified nano-silica.

3. The antiseptic oil according to claim 2, wherein In the preparation process of the monoalkoxy titanate, the molar ratio of the 2,6-dimethyl-4-heptanol to TiCl4 is 3-5:1, the pH of the modification reaction is 9-10, the temperature of the modification reaction is 150°C-180°C, and the time of the modification reaction is 1-2h; Preferably, in the preparation of the modified nano-silica, the temperature of the hydroxyl replacement reaction is 120° C.-180° C., the time of the hydroxyl replacement reaction is 30 min-50 min, and the molar ratio of fumed silica to 1,3-diphenyltetramethyldisilazane is 1-3:

1.

4. The anticorrosive oil according to any one of claims 1 to 3, wherein The organosilicon defoamer is selected from one or more of polydimethylsiloxane and polyethylene glycol siloxane, preferably polydimethylsiloxane; Preferably, the molecular weight of the organosilicon defoamer is 2000-3000 g / mol; Preferably, the antioxidant is selected from one or more of thiodiphenylamine, diphenylamine, and diisooctyldiphenylamine, preferably thiodiphenylamine.

5. The anticorrosive oil according to any one of claims 1 to 4, wherein Relative to 1 part by weight of the monoalkoxy titanate, the content of the dihydroxypropyl octadecanoate is 0.1-0.3 part by weight, the content of the silicone defoamer is 0.01-0.03 part by weight, the content of the antioxidant is 0.01-0.03 part by weight, the content of the modified nano-silica is 0.01-0.03 part by weight, the content of the nano-titanium dioxide is 0.01-0.03 part by weight, the content of the graphene is 0.01-0.03 part by weight, and the content of the aluminum tripolyphosphate is 0.01-0.03 part by weight.

6. An anti-corrosion material, characterized in that: The anti-corrosion material comprises an anti-corrosion base oil layer, an intermediate fiber layer and an outer protective layer, wherein the anti-corrosion oil forming the anti-corrosion base oil layer is the anti-corrosion oil according to any one of claims 1-5.

7. The anticorrosive material according to claim 6, wherein: The intermediate fiber layer is a fiber layer formed by one or more selected from polyester fibers, polyurethane fibers and polyamide fibers; Preferably, in the outer protective layer, relative to 100 parts by weight of polyethylene, the content of ethylene-vinyl acetate copolymer is 0.1-0.3 parts by weight, the content of benzotriazole is 0.2-0.8 parts by weight, the content of thiocarbamate is 0.3-0.6 parts by weight, the content of graphene is 5-10 parts by weight, the content of silicon powder is 6-10 parts by weight, the content of neodymium oxide is 2-5 parts by weight, and the content of aluminum tripolyphosphate is 0.1-0.5 parts by weight; Preferably, the molecular weight of the polyethylene is 2000-3000 g / mol; Preferably, the molecular weight of the ethylene-vinyl acetate copolymer is 1000-3000 g / mol; Preferably, the weight ratio of the structural units provided by ethylene to the structural units provided by vinyl acetate in the ethylene-vinyl acetate copolymer is 70-75:25-30; Preferably, the thickness of the anti-corrosion bottom oil layer is 2-3 mm, the thickness of the intermediate fiber layer is 2-3 mm, and the thickness of the outer protective layer is 2-5 mm; Preferably, the hydrophobicity of the base oil layer is 96%-98.8%, the tensile strength of the intermediate fiber layer is 10MPa-12MPa, the elongation at break of the intermediate fiber layer is 10%-15%, the elongation at break of the outer protective layer is 730%-760%, the tensile strength (circumferential / axial) of the outer protective layer is 28MPa-31MPa, the impact strength of the outer protective layer is 8J / mm, and the 3000h UV aging resistance tensile performance retention rate of the outer protective layer is 84-87%.

8. A method for preparing an anticorrosive material, characterized in that: The preparation method comprises: laying out an outer protective layer and an intermediate fiber layer and then pressing them, and coating an anti-corrosion base oil layer on the intermediate fiber layer after the pressing is completed, wherein the anti-corrosion oil forming the base oil layer is the anti-corrosion oil described in any one of claims 1-5.

9. The preparation method according to claim 8, wherein: The pressing method is hydraulic pressing; Preferably, the temperature of the hydraulic pressing is 50°C-90°C, and the pressure is 10-20 MPa.

10. The anti-corrosion material obtained by the preparation method according to claim 8 or 9.

11. Use of the anti-corrosion material according to any one of claims 6 to 7 and 10 in corrosion protection of marine steel materials.

Citation Information

Patent Citations

  • External protection device of corrosion prevention layer of pipeline or pile and processing method thereof

    CN106739189A